The Determinants of Indonesian Islamic Rural Banks' Non-Performing Financing - Agus Widarjono; Ari Rudatin (Global Review of Islamic Economics and Business, 2021)
Islamic bank encounters a high financing risk because of scheme contract using the profit-loss sharing system leading to an agency problem. The non-performing financing of Islamic rural banks as small Islamic banks in Indonesia is above the maximum threshold and is higher than that of conventional rural banks as their competitors. This paper investigates the impact of bank characteristic variables and macroeconomic variables on the non-performing financing of Islamic rural banks. Our study employs aggregate Islamic rural banks data, spanning from January 2009 to December 2018. Non-linear autoregressive distributed lag model (NARDL) is applied to address this issue. Capital adequacy ratio obviously increases impaired financing and income diversification clearly reduces non-performing financing. More interestingly, domestic output and inflation have an asymmetric effect on non-performing financing. Economic downturns increase non-performing financing but economic upturns have no impact on non-performing financing. Meanwhile, inflation deteriorates non-performing financing but deflation does not reduce non-performing financing.